The prospects of biofuels as a green solution towards sustainability - Hu, Wai Ching; Mohd Zahari, Fadhilah (2017)
Biofuel is an alternative, sustainable, environmental friendly and renewable source of energy.Biofuel has gained attention nowadays due to the potential of reduced environmental impacts as well as increased economic and social benefits. The purpose of this study is to examine the prospects of biofuel to the environment, economy and social.This study employs qualitative research method whereby the insight regarding biofuel was collected through interview with a practitioner in this sector.The findings show that biofuel causes less greenhouse gas (GHG) emissions and harmless to the environment.However, there are some biofuel which is made from crops can have negative environmental effects.There are serious impacts towards biodiversity conservation.This study found that it has positive impacts to the economy. By building the biofuel industries on the empty lands, this can generate economic benefits to the countries as the demand of biofuel is increasing. The new and existing biofuel industries can create and provide new job opportunities to the people. This can help them to improve and develop skills. As a result, their standard of living can be improved.However, the low awareness of biofuel in Malaysia reflects lack of policy to promote biofuel.Consequently, awareness on the potential of biofuel should be implemented in order to support the sustainability agenda of the country.